Pemahaman Kritis Terhadap Naratif Iklan Rokok Djarum 76: Sebuah Eksplorasi Analisis Wacana Kritis - Justiani Intan Lahagu; Mustika Wati Siregar; Theresa Da Silvia Sihite; Yesi Jesika Br Sitepu (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The use of critical theory as an analytical tool, especially in the context of the use of words in the Djarum 76 cigarette advertisement which raises critical questions. The aim of this research is first, to reveal the implied meaning in the Djarum 76 cigarette advertisement through a critical discourse analysis approach. Second, to explain the social meaning of the use of words in the advertisement in the context of general society. The method used is a critical discourse approach with an analytical descriptive method, which aims to describe the phenomena contained in the advertisement. This research limits its focus to the Djarum 76 cigarette advertisement. The research results show that the Djarum 76 cigarette advertisement has a distinctive presentation style with the use of humorous words but contains implied meaning. These words have become part of popular culture and are able to attract people's attention. Apart from that, Djarum 76 cigarette advertisements are also known for their distinctive jargon, such as "wani piro?" and "I'll give you one wish", as well as Uncle Jin's style which contains social criticism implied in these words.